Obituary: Ole Crumlin-Pedersen (24 February 1935 - 14 October 2011) - Tinna Damgård-Sørensen (EXARC Journal, 2012)
On 14 October 2011, Ole Crumlin-Pedersen passed away after a long period of illness, aged 76. Ole Crumlin-Pedersen, born 24 February 1935 in Hellerup, Denmark dedicated his life to maritime cultural heritage, maritime archaeology and old ships. He was a pioneer who, through his professional engagement and an almost unbelievable capacity for work, developed an entirely new area of archaeological fieldwork. He changed our view of the world of the past, and gave us new glasses with which to view history. The Viking Ship Museum at Roskilde stands as the most striking trace of what he leaves behind.